Analysis of Students' Learning Difficulties in Learning Mathematics at Elementary Schools - Yulita .; Siti Quratul Ain (AL-ISHLAH: Jurnal Pendidikan, 2021)
This study aims to know the difficulty in learning mathematics experienced by fourth-grade students of SDN 169 Pekanbaru regarding understanding concepts. This study uses descriptive qualitative research with primary data sources from teachers and students of class IV SDN 169 Pekanbaru and secondary data sources obtained from documents and archives supporting learning in class IV to analyze student learning difficulties in mathematics in class IV SDN 169 Pekanbaru. The data collection techniques were obtained through interviews, observation and documentation techniques. To obtain the validity of objective data in qualitative research, the researcher will use source triangulation and technical triangulation. This study uses data analysis techniques Miles and Huberman, namely data collection, data reduction, data presentation and data inference. The results showed students' difficulties in using concepts, difficulties in using principles, and difficulties solving verbal problems. The factors that cause students to experience learning difficulties in learning mathematics in class IV SDN 169 Pekanbaru include internal and external factors. The factors that come from within students (internal) include physical factors, psychological factors (intelligence, attention, interest, talent, motivation), and fatigue. In contrast, the factors that come from outside the student (external) include family factors, school factors (learning methods, learning tools, teaching methods), and community factors.